Pengaruh Suhu Pengeringan dan Tingkat Ketebalan Irisan Wortel Terhadap Mutu Tepung Wortel - Risya Delfira Cahyani Effendi; Tamrin Tamrin; Muhammad Amin (abe.fp.unila.ac.id, 2022)
This research is about the effect of temperature and thickness level of carrot slices on the quality of carrot flour. Processing and consumption of carrots is still limited to fresh carrots and carrot juice. The advance of technology makes people demand alternatives to fresh materials that have a short shelf life and are less practical in processing them into a product. Carrot shelf life is short resulting in many carrots wasted. Therefore, an alternative is needed to process carrots into flour. The purpose of this study was to study the effect of temperature and thickness level of slices on the quality of carrot flour on water content, color, vitamin C content, and flour density. This research uses factorial completely randomized design (RAL) consisting of 2 treatments and 3 replications. First factor is temperatures of 50 ° C (T1), 70 ° C (T2), and 90 ° C (T3). The second factor is the thickness of the slices of 2 mm (A1), 4 mm (A2), and 6 mm (A3). The parameters observed were water content, color, vitamin C content, and density. The results obtained in this study were the water content obtained ranged from 13.15% - 18.74%. The resulting color resembles fresh carrots that is orange with a color value of 95.087. The content of vitamin C in carrot flour ranges from 0.4425 mg/g - 0.5508 mg/g. The density of carrot flour produced is close to each other in the range of 0.5133 g/cm3 - 0.5142 g/cm3. The difference in temperature and thickness affects the level of concentration and does not affect the content of vitamin C and flour density. The difference in thickness does not affect the color. Keyword: Carrot, Drying, Temperature, Thickness.